2018
DOI: 10.1111/papr.12734
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Cohort Analysis of DRG Stimulation for Failed Back Surgery Syndrome Pain Following Lumbar Discectomy

Abstract: Introduction Surgical lumbar discectomy is a commonly performed routine spinal procedure that is usually undertaken to alleviate lumbar radicular symptoms caused by a herniated intervertebral disc. Surgical lumbar discectomy can also lead to chronic postsurgical leg and/or back pain (failed back surgery syndrome [FBSS]), a condition that can be refractory to conventional medical management. Early clinical results on the use of dorsal root ganglion (DRG) stimulation for FBSS have supported the use of this treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 25 publications
3
30
0
6
Order By: Relevance
“…These pre‐ and post‐values roughly correspond to normalized values from patients with morbid chronic disease to healthy individuals, respectively . The patients included in Huygen et al showed an EQ‐5D increase from 0.31 to 0.50, similar to the findings in the recent Kallewaard et al publications, with index values increasing from 0.34 to 0.82 and 0.61 to 0.84 at 12 months, respectively, in the FBSS and non‐operated cohorts . Our patients pretreatment demonstrated a similar baseline of 0.30, however, the index score improved to 0.86, with four reporting maximal index values of 1.0.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…These pre‐ and post‐values roughly correspond to normalized values from patients with morbid chronic disease to healthy individuals, respectively . The patients included in Huygen et al showed an EQ‐5D increase from 0.31 to 0.50, similar to the findings in the recent Kallewaard et al publications, with index values increasing from 0.34 to 0.82 and 0.61 to 0.84 at 12 months, respectively, in the FBSS and non‐operated cohorts . Our patients pretreatment demonstrated a similar baseline of 0.30, however, the index score improved to 0.86, with four reporting maximal index values of 1.0.…”
Section: Discussionsupporting
confidence: 87%
“…Kallewaard et al also described, with bilateral L2 DRG leads, that stimulation relieved low back pain arising from post‐discectomy FBSS as well as from non‐operated discogenic pain . These patients were highly screened with diagnostic injections to specifically focus on discogenic pain, so in these cases placement of DRG‐S leads at the L2 spinal level may represent a treatment focal point for pain originating from the intervertebral disc . Another report documented 61% back pain relief with high frequency DRG/nerve root stimulation at either the L2 or T9 levels, with patients generally preferring T9 lead placement .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Our prospective study with DRG L2 stimulation in a highly selected group of patients with CD-LBP showed a promising result after 12 months. 16 Further studies are needed to define if there is a place for neurostimulation in CD-LBP in non-operated patients and to find what place it should have in the treatment algorithm of CD-LBP.…”
Section: What Did We Find In Our Studies?mentioning
confidence: 99%
“…menos conexões centrais), implicando em pouca ou nenhuma habituação, o que pode conferir vantagem adicional ao método sobre outras formas de modulação. Taxas bem-sucedidas de alívio da dor foram observadas em outras séries de casos (Huygen et al, 2017, Mol et al, 2017, van Bussel et al, 2017, Eldabe et al, 2018, Falowski et al, 2018, Hassanain et al, 2018, Kallewaard et al, 2018, Skaribas et al, 2018 bem como em alguns relatos de casos (Garg et al, 2015, Rowland et al, 2016, Zuidema et al, 2016, Maino et al, 2017, Zuidema et al, 2017, Giordano et al, 2018, Goebel et al, 2018, Groenen et al, 2018. Uma série com 217 pacientes avaliados retrospectivamente num estudo multicêntrico demonstrou 66,9% de alivio da dor medida pela EVN durante a triagem quando comparada a linha de base em um grupo de pacientes apresentando diversos tipos de dor neuropática .…”
Section: Avaliação Da Intensidade Da Dorunclassified